Mind Mapping for Dummies - Florian Rustler (--For dummies., 2013)
Unlock your brain\'s potential using mind mapping. Mind Mapping for Dummies explains how mind mapping works, why it is so successful and the many ways in which it can be used. It takes readers through the wide range of approaches to mind mapping, looks at the available mind mapping software options and investigates advanced mind mapping techniques for a range of purposes, including exam revision, improving memory, project management and maximizing creativity. All the mind maps in the book are presented in full color.